Rekacipta Tradisi Betawi: Sisi Otoritas dalam Proses Nasionalisasi Tradisi Lokal - Yasmine Zaki Shahab (Antropologi Indonesia, 2001)
These days there are many who believe that the Betawi will become mere legends of an ethnic group that once lived in Jakarta. Even as they are aware of the existence of Jakarta's indigenous people, they are swept by the myth that this ethnic group has been marginalized, and gradually losing its identity as a result of development. However, the voice of the Betawi is now being heard-including their demand that the office of Governor of Jakarta be held by a Betawi-leading many to ask: 'Who are they?' What the Betawi are doing is in contrast to the myths surrounding them. The author sees the matter as a contradicting viewpoint of Betawi. Although many believe that this ethnic group is becoming marginalized and in the process of disappearing, the author believes the opposite is true. The Betawi are becoming more noticeable; and they are playing a larger role in Jakarta's history. They are not in the process of disappearing, but are re-appearing. They are not losing their identity; instead, they are creating, and in fact have found and are actively expressing Betawi identity as a means of representing their existence. This has been going on since the 1970's in many aspects of life. This article focuses on art as one aspect. The author believes has been given much attention by actors in the invention of tradition. The outcome has been a qualitative and quantitative improvement in the existence of the Betawi ethnic group, which has in turn raised the attention of those any deal with the Betawi people. Several issues are discussed here: when did all these begin among the Betawi? What triggered the process? Who are involved, and who, especially, are the active players? If art is reinvented, are the effects limited to art and matters of identity and self-representation; or are there wider ranging consequences? If the latter is the case, then the author expects the use of cultural aspects for non-cultural ends. How will this take place? With a focus on the actors of reinvention, the question to be addressed is who holds authority in the reinvention of tradition in efforts to achieve non-cultural goals through a cultural approach, and how does this come about?